2002
DOI: 10.1080/01612840290052758
|View full text |Cite
|
Sign up to set email alerts
|

What Parents of Mentally Ill Children Need and Want From Mental Health Professionals

Abstract: Child psychiatric hospitalization is a time of crisis for the parents of a child with a mental disorder. Prior to hospitalization, the child's problematic behavior has escalated. Parents have various types of contact with mental health professionals prior to, during, and after the hospitalization, which influence their ability to care for their child. This paper reports a qualitative descriptive study of what parents need and want from mental health professionals during this time frame. During the study, paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…The theme of worrying about the rest of the family is consistent with findings from previous studies in which caregivers shared concerns about the impact that the child's mental health needs had on the family (Lam & Mackenzie, 2002;Lefley, 1997;Lovenfosse & Viney, 1999). Also, the theme of being burdened and exhausted resonated with findings from other research studies (Goldberg-Arnold et al, 1999;Peters & Jackson, 2009;Scharer, 2002) in which caregivers reported being socially isolated due to caregiving demands, giving up employment in order to cope with their children's needs, and having multiple mental health appointments and calls from schools because of behavioral problems (Nelson, 2002;Peters & Jackson, 2009;Smith & Smith, 2000;Yantzi et al, 2006). Our study findings about the benefits of support groups with others going through similar experiences reinforce the work of other researchers who reported that access and participation in support groups helped to increase caregivers' ability to understand themselves and others, to talk and be listened to without judgment, to put their problems into perspective, and to make use of the group to provide an outlet for stress relief.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The theme of worrying about the rest of the family is consistent with findings from previous studies in which caregivers shared concerns about the impact that the child's mental health needs had on the family (Lam & Mackenzie, 2002;Lefley, 1997;Lovenfosse & Viney, 1999). Also, the theme of being burdened and exhausted resonated with findings from other research studies (Goldberg-Arnold et al, 1999;Peters & Jackson, 2009;Scharer, 2002) in which caregivers reported being socially isolated due to caregiving demands, giving up employment in order to cope with their children's needs, and having multiple mental health appointments and calls from schools because of behavioral problems (Nelson, 2002;Peters & Jackson, 2009;Smith & Smith, 2000;Yantzi et al, 2006). Our study findings about the benefits of support groups with others going through similar experiences reinforce the work of other researchers who reported that access and participation in support groups helped to increase caregivers' ability to understand themselves and others, to talk and be listened to without judgment, to put their problems into perspective, and to make use of the group to provide an outlet for stress relief.…”
Section: Discussionmentioning
confidence: 63%
“…Like caregivers of children with physical disabilities, the caregivers in this study described a protracted, convoluted, and frustrating process of accessing care for their children (Jackson et al, 2008;Lutenbacher et al, 2005;Parminder et al, 2005;Rosenwald & Bronstein, 2008;Scharer, 2002;Smith & Smith, 2000). The theme of struggling with care systems mirrors findings from Scharer (2002), who reported that caregivers of children in a psychiatric inpatient unit experienced urgent needs for timely, accurate, and complete information regarding their children's illness and desired support from professionals, which they often did not get (Scharer, 2002).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…al, 1999;Brown & Jemmott, 2002;Boyer et. al, 2000;Scharer, 2002;Tarrant & Gregory, 2003). One study, which explored Hmong women's concerns about pregnancy and childbirth, documented culturally influenced issues of birth control and fear of miscarriage (Jambunathan & Stewart, 1995) and these findings supported continuing education programs for health workers.…”
Section: Ethnomethodologymentioning
confidence: 97%